Nutritional Stability of Molasses Multinutrient Soft During Storage - Syarifuddin; Jirfan Dawanto; Malik Makmur; Asmawati; Muhammad Idrus; Sri Firmiaty; Solihin Fikriandi; Andi Syahraeni Dg. Te’ne (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Molasses Multinutrient Soft (MMS), an innovative alternative livestock feed formulated from agro-industrial waste products such as molasses, tofu dregs, coconut cake, rice bran, salt, and a mineral mix, was evaluated for nutrient stability during storage. Feed storage was conducted on a laboratory scale. This study employed a completely randomized design across 0, 10, 20, and 30-day storage periods, revealing that storage significantly influenced (p < 0.05) key quality parameters, including moisture, dry matter, organic matter, ether extract, and acid-insoluble ash. While crude protein and nitrogen-free extract remained stable, significant changes (p < 0.05) were observed in fiber fractions (neutral detergent fiber, acid detergent fiber, and hemicellulose) and phosphorus content. These alterations, predominantly driven by microbial activity and environmental conditions, suggest that MMS maintains safe storage limits for up to 30 days. A strong correlation between moisture and dry matter was observed during storage, a key attribute that determined the feed's nutritional quality. This study offers valuable insights into the post-production quality of alternative feeds, underscoring MMS's potential as a viable and promising feed option for smallholder livestock farmers, particularly under minimal storage conditions. Further investigation is required regarding the effects of prolonged feed storage on the physical and chemical characteristics of MMS. Contribution to Sustainable Development Goals (SDGs):SDG 2:   Zero Hunger;  SDG 12: Responsible Consumption and Production; SDG 15: Life on Land